Crime and conflicts in Africa: consequences of corruption? - Simplice A. Asongu; Oasis Kodila-Tedika (African Governance and Development Institute (AGDI), 2013)
With earthshaking and jaw-breaking levels of corruption in the African continent, the question on the extent to which corruption influences crime still remains unanswered. This paper assesses the effect of corruption (corruption-control) in 38 African countries using updated data. We find that, crime is highly positively (negatively) correlated with corruption (corruption-control). The potential mitigation effect (by corruption-control) is higher than the corresponding positive effect of corruption, implying, corruption-control offsets crime emanating beyond the corruption mechanism (inter alia, other poor governance mechanisms). The relationship is statistically strong when controlling for the number of police officers, age dependency, per capital economic prosperity, level of education, government effectiveness and population density. Given that crime is proxied by the level of organized internal conflict, the findings also sustain the substantial role of corruption in the birth and propagation of conflicts within and across Africa. Policy implications are discussed.
Keywords: F52; K42; O17; O55; P16; 330; Security; Corruption; Crime; Conflicts; Africa